Physico-Chemical Properties and Species Diversity of Crustacean Zooplankton in Ikarama River, Yenagoa, Bayelsa State, Nigeria - Thankgod, Didi Osomuze; Anyalogbu, Ernest Anayochukwu; Ogidi, Odangowei Inetiminebi (International Journal of Scientific Research in Biological Sciences, 2024)
This study was aimed at investigating the physicochemical properties and species diversity of crustacean zooplankton in Ikarama River. It was carried out from 16th of September to 18th of August. Four stations were examined consecutively, moving from a point higher up in the stream to a point lower down. The distance between each station was approximately 400 metres. The water was tested for seventeen different physicochemical parameters according to the AOAC`s official techniques of analysis and the Standard Method for the Examination of Water and Wastewater. The Air and water surface temperatures results ranged from 28.0oC to 29.5oC. Transparency (1.8 m – 1.9 m) and Total suspended solids (70.5 mg-1-75.0 mg-1) showed inverse relationship. Depth ranged from 65 cm to 80 cm, while turbidity ranged from 50 NTU to 55 NTU. TDS ranged between 65 mg-1 and 72 mg-1, total solids ranged between 6.1 mg-1 and 7.0 mg-1. pH values ranged from 5.5 to 6.5. Dissolved oxygen value ranged from 8.5 mg-1 to 10.0 mg-1, while the BOD5 (2.9 mg-1 and 4.5 mg-1) indicated no form of pollution or stress on the water body. Conductivity and chloride values ranged from 9.0 ?scm-1 to 10.7 ?scm-1 and 60.0 mg-1 to 60.5 mg-1 respectively. The water of River Ikarama was relatively low in its assemblage of crustacean zooplankton. A total of 11 crustacean zooplankton species belonging to 9 genera in 5 families and 3 orders were obtained during the study period. The family Cyclopoidae was the dominant group in the order Cyclopoida while the family Chydoridae was the only family recorded in the order Cladocera. All the eleven taxa were recorded in all stations. In all stations, the Copepoda were more abundant than the Cladocera and Harpacticoida. The study also established that the overall density of copepod was not significantly different (P<0.05) between the study stations. All the species recorded were almost evenly distributed in all the stations. No evidence of water pollution recorded in any of the stations sampled. The river was relatively homogenous across the different stations and all the parameters were within the WHO recommended standards for domestic use.